Head‐to‐Head Comparison Between Phosphatidylethanol Versus Indirect Alcohol Biomarkers for Diagnosis of MetALD Versus MASLD: A Prospective Study - Tavaglione, Federica; Amangurbanova, Maral; Yang, Alexander H.; Tincopa, Monica A.; Ajmera, Veeral; Richards, Lisa; Butcher, Christian; Hernandez, Christie; Madamba, Egbert; Singh, Seema; Bettencourt, Ricki; Sirlin, Claude B.; et al. (Alimentary pharmacology & therapeutics, 2025)
ABSTRACT Background The current subclassification of steatotic liver disease (SLD) relies on validated questionnaires, such as Alcohol Use Disorders Identification Test (AUDIT) and Lifetime Drinking History (LDH), which, while useful, are impractical and lack precision for their use in routine clinical practice. Phosphatidylethanol (PEth) is a quantitative, objective alcohol biomarker with high sensitivity and specificity. Aims To assess the diagnostic accuracy of PEth for differentiating metabolic dysfunction and alcohol‐associated liver disease (MetALD) from metabolic dysfunction‐associated steatotic liver disease (MASLD) in a large, population‐based, prospective, multiethnic cohort of individuals with overweight or obesity. Methods This is a cross‐sectional analysis of a prospective study including 374 adults with overweight or obesity residing in Southern California who had SLD as defined by MRI‐PDFF ≥ 5%. The clinical research visit included medical history, biochemical and PEth testing, standardised validated questionnaires (including AUDIT and LDH), physical examination, and advanced imaging using MRI‐PDFF and MRE. Results Among 374 adults with SLD, the prevalence of MASLD, MetALD, and ALD was 90.1%, 6.4%, and 3.5%, respectively. PEth had a robust diagnostic accuracy in the detection of MetALD (AUROC 0.81, 95%CI 0.73–0.89) and the Youden cut‐off was 25 ng/mL. In head‐to‐head comparative efficacy analysis, PEth was both statistically and clinically superior to all previously used indirect alcohol biomarkers for diagnosing MetALD, including aspartate aminotransferase/alanine aminotransferase ratio, mean corpuscular volume, gamma glutamyltransferase, and ALD/NAFLD index (p < 0.05). Conclusions PEth outperforms previously used non‐invasive tests in differentiating MetALD from MASLD and has the potential to change clinical practice by enhancing the subclassification of SLD. Using a well‐phenotyped prospective cohort with systematic assessment through MRI‐PDFF, MRE, and PEth testing, this study demonstrates that PEth is an accurate, quantitative, objective alcohol biomarker for detecting and differentiating MetALD from MASLD, and outperforms previously available indirect alcohol biomarkers.